Almayer's Folly: A Story of an Eastern River - Conrad, Joseph, 1857-1924 (Salt Lake City, UT : Project Gutenberg, 1996)
"Almayer's Folly: A Story of an Eastern River" by Joseph Conrad is a novel published in 1895. Set in the Borneo jungle, it follows Dutch trader Kaspar Almayer, who dreams of finding hidden gold and building wealth. Married to a native Malayan woman with a mixed-heritage daughter Nina, Almayer's obsessive pursuit of riches leads to tragedy when a Malayan prince arrives and falls in love with Nina. The story explores colonialism, family loyalty, and the devastating consequences of impossible dreams. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Almayer%27s_Folly
Release date is 1996-11-01
Transcribed from the 1915 T. Fisher Unwin Ltd. edition by David Price
Keywords: Dutch -- Borneo -- Fiction; Didactic fiction; Imperialism -- Fiction; Psychological fiction; Trading companies -- Fiction; Lingard, Tom (Fictitious character) -- Fiction; Borneo -- Fiction